The Effect of Digital Marketing, Electronic Word of Mouth, and Brand Trust on Purchasing Decisions of Kopi Kenangan in Batam City - Stiven Dedly; Nur Elfi Husda (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to examine the effect of digital marketing, electronic word of mouth (e-WOM), and brand trust on purchasing decisions at Kopi Kenangan in Batam City.  An explanatory quantitative method was used with a sample of 105 Kopi Kenangan customers in Batam, selected purposively. Data were collected through a 5-point Likert scale questionnaire measuring four main constructs, then analysed using multiple linear regression. Classical assumption tests (normality, multicollinearity, heteroscedasticity) and reliability validity tests (Pearson r, Cronbach's Alpha) were conducted to ensure data quality. The results of the analysis show that the three independent variables together explain approximately 67.1% of the variation in purchasing decisions. Partially, e-WOM made the largest contribution, followed by brand trust and digital marketing. The estimated regression equation is: Y = 0.210 + 0.104X1 + 0.725X2 + 0.365X3. These findings indicate that online customer opinions and brand trust are the main drivers of purchasing decisions, while digital promotion plays a supporting role through indirect channels. The practical implication is that Kopi Kenangan Batam needs to strengthen positive e-WOM and brand trust while maintaining visibility through digital marketing.